2020
DOI: 10.5430/ijfr.v11n4p165
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Benefits and Difficulties When Applying IFRS in Vietnam: From Business Perspective

Abstract: While many countries around the world have adopted IFRS at different levels, Vietnam is in the process of IFRS adoption by 2022. The study was conducted through the survey of 119 directors and accountants to estimate the benefits and difficulties of applying IFRS in Vietnam. The forecast content include (i) Business benefits; (ii) Benefits for investors; (iii) Benefits to policy makers; (iv) Benefits for state management agencies; (v) Challenges of applying IFRS. By regression analysis, the forecast results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…According to earlier research (Golubeva 2020;Mita et al 2018), there may be a positive correlation between the adoption of IFRS and the environment for EDBs due to the potential advantages for investors, such as an improvement in accounting quality and comparability of financial data. Thus, as cited by Bui et al (2020), when financial statements are reported using the same accounting principles, the results provided can guarantee comparability, helping investors' analyses and reducing possible costs for information processing. All these arguments lead to the following hypothesis: H1: There is an association between IFRS adoption and a friendly business climate measured by EDB.…”
Section: Research Hypothesesmentioning
confidence: 90%
See 1 more Smart Citation
“…According to earlier research (Golubeva 2020;Mita et al 2018), there may be a positive correlation between the adoption of IFRS and the environment for EDBs due to the potential advantages for investors, such as an improvement in accounting quality and comparability of financial data. Thus, as cited by Bui et al (2020), when financial statements are reported using the same accounting principles, the results provided can guarantee comparability, helping investors' analyses and reducing possible costs for information processing. All these arguments lead to the following hypothesis: H1: There is an association between IFRS adoption and a friendly business climate measured by EDB.…”
Section: Research Hypothesesmentioning
confidence: 90%
“…Numerous studies on the effects of adopting the International Financial Reporting Standards (IFRS), as well as its advantages and challenges, have been conducted over the past 20 years (Opare et al 2019;Bui et al 2020;Boolaky et al 2020). Due to the conflicting results of the many studies, it is still difficult for the accounting literature to credit conclusive impacts as to the advantages of implementing the IFRS (Ball 2006;Brown 2011).…”
Section: Introductionmentioning
confidence: 99%
“…systematically examines why a country does not fully, partially or not adopt IFRS and classifies these factors into essential categories [ 76 ]. finds that private companies using IFRS have more growth opportunities, have more leverage, are more appreciated from the outside, increase the ability to raise external capital by issuing public bonds or equity, has more revenue and international operations [ 39 ]. forecast the benefits of applying IFRS for businesses, investors; policymakers; and state management agencies [ 2 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…examine the causal relationship between accountants' awareness and willingness to apply IFRS [ 38 ]. analyses the applicability of IAS/IFRS [ 39 ]. estimate the benefits and disadvantages of applying IFRS.…”
Section: Introductionmentioning
confidence: 99%
“…The results in these two countries might not repeat in Vietnam, which prompts us to investigate the link in the new setting. Second, although some research has been done on the adoption of IFRS in Vietnam (Bui et al, 2020;Tran et al, 2019), but, in general, the legal framework in Vietnam regarding FSC is still incomplete, and full IFRS adoption has not been implemented in Vietnam. On March 23, 2019, the Ministry of Finance released the IFRS Market concentration and financial statement application roadmap for Vietnam.…”
mentioning
confidence: 99%